Polityka etniczna Republiki Łotewskiej (Politeja, 2016)
Ethnic Policy of Republic of LatviaThis article aims to analyze the factors and significance of particular subjects and instruments of the Latvian ethnic policy. It will be examined in the context of relationships occurring between Latvia’s policy on ethnic minorities, the attitude of the Russian-speaking minority and the Russian Federation’s foreign policy on its fellow-countrymen abroad. We will also attempt to answer the question of how the Latvian ethnic policy influences horizontal interrelations between the state’s individual ethnic groups – whether it alleviates social tensions or intensifies them.